Entry inhibition of HSV-1 and -2 protects mice from viral lethal challenge - Clementi, Nicola; Criscuolo, Elena; Cappelletti, Francesca; Quaranta, Paola; Pistello, Mauro; Diotti, Roberta A.; Sautto, Giuseppe A.; Tarr, Alexander W.; Mailland, Federico; Concas, Daniela; Burioni, Roberto; Clementi, Massimo; et al. (Elsevier, 2017)
The present study focused on inhibition of HSV-1 and -2 replication and pathogenesis in vitro and in vivo, through the selective targeting of the envelope glycoprotein D. Firstly, a human monoclonal antibody (Hu-mAb#33) was identified that could neutralise both HSV-1 and -2 at nM concentrations, including clinical isolates from patients affected by different clinical manifestations and featuring different susceptibility to acyclovir in vitro. Secondly, the potency of inhibition of both infection by cell-free viruses and cell-to-cell virus transmission was also assessed. Finally, mice receiving a single systemic injection of Hu-mAb#33 were protected from death and severe clinical manifestations following both ocular and vaginal HSV-1 and -2 lethal challenge. These results pave the way for further studies reassessing the importance of HSV entry as a novel target for therapeutic intervention and inhibition of cell-to-cell virus transmission.